Three-Dimensional Modeling of Thermal-Mechanical Behavior of Accident Tolerant Fuels - Zeng, Zitao; Pan, Yongyu; Chen, Xi; Zhang, Chunyu; Yin, Chunyu; Gao, Shixin; Zhou, Yi; Zhang, Jie; He, Xiujie; Yuan, Cenxi (Frontiers in Energy Research, 2021)
Considering the safety issues of the traditional UO2-Zr fuel, a variety of accident-tolerant fuel (ATF) candidates have been proposed in recent years. Among the several ATFs, U3Si2 and UN are the two promising candidates for fuel owing to their high thermal conductivity and high uranium density. The FeCrAl alloy and the SiC/SiC composite material are the two promising candidates for cladding owing to their high oxidation resistance and high strength. In order to quantitatively evaluate the performance of ATFs, this study summarizes the physical models of typical ATF cladding materials (FeCrAl and SiC) and pellet materials (UN and U3Si2). Then a three-dimensional nonlinear finite element method is applied to simulate the thermal-mechanical behavior of several typical fuel-cladding combinations, including UO2-FeCrAl, UN-FeCrAl, U3Si2-FeCrAl, U3Si2-Zr and U3Si2-SiC. The important physical quantities, such as the fuel centerline temperature, the deformation of the pellet and the cladding as well as the pellet-cladding mechanical interaction (PCMI) were studied. The fission gas release model was also verified and improved.